ANALISIS KESESUAIAN PENJAMINAN MUTU ADMINISTRASI PERSURATAN DAN KEARSIPAN DENGAN STANDAR NASIONAL PENDIDIKAN DI MTSN 4 SIDOARJO - Abd Hamid; Muhammad Rendi Saputra; Mochammad Misbahul Alam; Sahudi Sahudi; Lilik Huriyah (STKIP Pesisir Selatan, 2026)
Correspondence and records management are essential components in supporting effective educational governance. This study aims to describe the implementation of quality assurance in correspondence and records administration at MTsN 4 Sidoarjo and to analyze its conformity with the National Education Standards (NES), particularly the management standards. The research employed a qualitative approach using a case study design. Data were collected through observations, interviews, and documentation, and analyzed using the interactive model of Miles, Huberman, and Saldaña, which includes data condensation, data display, and conclusion drawing. The findings indicate that MTsN 4 Sidoarjo has utilized the SRIKANDI application, Electronic Signatures (TTE), and a numerical records classification system to support administrative management. However, the implementation of quality assurance has not been fully optimized due to the absence of written Standard Operating Procedures (SOPs), the lack of full integration between administrative systems, and the unavailability of documented evaluation instruments. The novelty of this study lies in its analysis of the conformity of correspondence and records administration practices with the National Education Standards from the perspective of administrative quality assurance in Islamic secondary schools.